KATEGORI KEPEMIMPINAN TRANSFORMATIONAL - Bakhtiar Bakhtiar (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2019)
Transformational leadership cannot be separated from four characteristics of leadership behavior. The four elements are idealized influence, inspirational motivation, intellectual stimulation, individualized consideration. If a leader fulfills one of the four elements of leadership behavior characteristics, then the leader can be categorized as transformational leadership. The leader is categorized as ideal transformational leadership, if he is only prominent in idealized influence, or as transformational leadership that is inspiring if it only stands out on inspirational motivation. A leader can also fulfill the category of more than one element, can be two, three or fulfill his decency if it meets the four elements, it will be a very good transformational leadership. So that can be categorized as transformational leadership is very dependent on fulfilling the elements of transformational leadership.